2019 IEEE 21st Conference on Business Informatics (CBI) 2019
DOI: 10.1109/cbi.2019.10093
|View full text |Cite
|
Sign up to set email alerts
|

COOC: An Agile Change Management Method

Abstract: Successful completion of the Industry 4.0 or Future Industry programs requires support for women and men to drive them. The challenge of aligning skills is complemented by the modernization of their practices and tools. All businesses are changing and change management techniques have become standard practice in most organizations. However, the so-called "traditional" methods are limited and it is now proposed change management methods called "agile", borrowing the philosophy of agile development methods to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…However, the authors argued whether adopting the Industry 4.0 technologies increase agility in a dynamic way [138,139], or whether adopting the Industry 4.0 technologies presents a change management challenge [140]. Moreover, it is suggested that the change induced by adopting Industry 4.0 technologies is not ordinary but rather a radical change in culture, structure and operations of organizations [139,[141][142][143]. Thus, only organizations which develop a nascent capability of agility will be better off by adopting Industry 4.0 technologies [107,[144][145][146].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%
“…However, the authors argued whether adopting the Industry 4.0 technologies increase agility in a dynamic way [138,139], or whether adopting the Industry 4.0 technologies presents a change management challenge [140]. Moreover, it is suggested that the change induced by adopting Industry 4.0 technologies is not ordinary but rather a radical change in culture, structure and operations of organizations [139,[141][142][143]. Thus, only organizations which develop a nascent capability of agility will be better off by adopting Industry 4.0 technologies [107,[144][145][146].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%
“…Other strong candidates for automation include repetitive tasks as this allows higher quality and production stability (Birkel et al, 2019;Pradhan and Agwa-Ejon, 2018). Various publications refer to employee fears that I4.0 technologies will take away their jobs (Eimontaite et al, 2019;Hahm, 2018;Horv ath and Szab o, 2019;Klumpp et al, 2019;Le Grand and Deneckere, 2019;Mora Sanchez, 2019;Pradhan and Agwa-Ejon, 2018).…”
Section: Feeling Of Inadequacymentioning
confidence: 99%
“…When participating in the development and implementation process, employees also have the opportunity to influence the features of the technology to better fit their needs and limitations. This promotes a sense of ownership (Le Grand and Deneckere, 2019). The great majority of industrial practitioners would be more inclined to use a technology that they had either designed or been consulted about during the implementation process (Kaasinen et al, 2019;Le Grand and Deneckere, 2019).…”
Section: Participationmentioning
confidence: 99%
See 2 more Smart Citations